On Power Generalized Akash Distribution with Properties and Applications - Samuel Aderoju,; Isaac Adeniyi, (Journal of Statistical Modeling and Analytics (JOSMA), 2022)
A new lifetime model known as power generalized Akash distribution (PGAD), which extends generalized Akash (GA) distribution has been proposed in this paper. The PGAD was inspired by the wide use of the Akash and GA distributions in various applied areas. Some structural characteristics of the new model were studied such as moments, reliability, hazard rate function, survival function, Renyi entropy measure and order statistics. The parameters of the model were obtained via the maximum likelihood estimation method. The flexibility and importance of the new distribution has been illustrated by its applications to two real datasets. Using BIC, AIC and 2Loglikelihood, it is obvious that the PGAD is more effective than Topp-Leone Lomax (TLLo), Generalized Akash (GA), Power Pranav (PP) and Power Transformed Power Inverse Lindley (APTPIL) distributions in modelling real lifetime data.